The Effect of Overhead Passing Practice with the Target Ring Method on Volleyball Passing Accuracy - M. Imamah Bagas Saputera; Agung Wahyudi (Universitas Negeri Semarang, 2026)
The overhead passing technique is one of the most important basic techniques in volleyball because it helps organize attacks and maintain the flow of the game. However, during training, some athletes still struggle to control the direction and accuracy of the ball during overhead passes. This study aims to determine the effect of overhead passing training with a target ring on the accuracy of overhead passing among extracurricular volleyball athletes. This study used an experimental design with a one-group pretest-posttest. The subjects were 20 extracurricular volleyball athletes at State High School 1, Pegandon. Data collection was conducted using an overhead passing skill test. The data were then analyzed using a paired-samples t-test to determine the difference in results before and after treatment. The results showed an increase in overhead passing ability after training with a target ring. The average pretest score of 8.85 increased to 15.25 in the posttest. The results of the paired-samples t-test showed a p-value of 0.000 (< 0.05), indicating a significant difference between the pretest and posttest scores. Thus, it can be concluded that overhead passing training using a ring target significantly improves the accuracy of overhead passing among extracurricular volleyball athletes.